Oxygen Independent DNA Interstrand Cross-Link Formation by a Nucleotide Radical - Hong, Seok (2006)
A 5-(2′-Deoxyuridinyl)methyl radical (1) was independently generated from three photochemical precursors and is the first example of a DNA radical that forms interstrand cross-links. Oxygen labeling experiments support generation of 1 by all precursors. Interstrand cross-links are produced upon irradiation of DNA containing any of the precursors. Cross-linking occurs via reaction with the opposing 2′-deoxyadenosine and is independent of O(2). The independence of cross-link formation on O(2) is explained by kinetic analysis, which shows that the radical reacts reversibly with O(2). Examination of the effects of glutathione on cross-link formation under anaerobic conditions suggests that adoption of the syn-conformation by 1 is the rate-limiting step in the process. Interstrand cross-link formation is reversible in the presence of a good nucleophile. The stability of the interstrand cross-link suggests that the isolated molecule is a rearrangement product of that formed in solution. The rearrangement is a consequence of the isolation procedure but also occurs slowly in solution. Oxygen independent cross-link formation may be useful for the purposeful damage of DNA in hypoxic tumor cells, where O(2) is deficient.